The effect of age on the outcomes of cementless mobile bearing unicompartmental knee replacements - Mohammad, HR; Mellon, S; Judge, A; Dodd, C; Murray, D (Springer Nature, 2021)
Purpose Unicompartmental Knee Replacements (UKR) are being performed in patients with increasing demands and life expectancies with surgical concerns that cemented fixation will not last. Cementless fixation may offer a solution, but the results in different age groups have not been assessed. The effect of age at surgery on the outcomes of cementless UKRs was investigated. Methods A prospective cohort of 1000 medial cementless mobile bearing UKR were analysed. Patients were categorised into four age groups (< 55, 55 to < 65, 65 to < 75 and ≥ 75 years). Implant survival was assessed using endpoints reoperation, revision and major revision requiring revision knee replacement components. Functional outcomes were assessed. Results 10 year cumulative revision rate for the < 55, 55 to < 65, 65 to < 75 and ≥ 75 groups were 2.1% (CI 0.6–6.1), 1.8% (CI 0.6–5.3), 3.2% (CI 1.5–6.5) and 4.1% (1.7–9.6) with no differences between groups (p = 0.52). Two of the 22 revisions were considered major. The 10 year cumulative reoperation rates were 4.5% (CI 2.0–10.0), 3.0% (CI 1.3–6.5), 3.8% (CI 2.0–7.1) and 4.1% (CI 1.7–9.6) with no differences between groups (p = 0.81). The 10 year median Oxford Knee Scores were 42.5, 46.5, 45 and 42.5, respectively. The 10 year median Objective American Knee Society Scores were 95 for all age groups. Conclusion The cementless mobile bearing UKR has low reoperation and revision rates and similar functional outcomes in all age groups. Cementless UKR should be used in all age groups and age should not be considered a contraindication. Level of evidence III.